PENGEMBANGAN KERATIVITAS SISWA/I DAN GURU SDN 32 TIGO SUKU PANINJAUAN, DENGAN MEMANFAATKAN MEDIA KALENG-KALENG BEKAS SEBAGAI APRESIASI DAN KREASI DALAM SENI RUPA - Intan Tursina; Puti Andam Dewi; Alfitri Yana Yunita; Della Oktavinoarti (Awal Bros Journal of Community Development, 2024)
Fine arts education in schools is a medium for talent development, thinking development and creativity development, for which students who not only understand what art is but how it is applied. Art education is one of the elements that refine a person's characteristics. Based on this reality, it is important to provide appreciation through art education, especially drawing and coloring for students and teachers by utilizing the media of used cans. The first step taken in the development of creativity painting activities is to explain the meaning of fine arts and their division, then an introduction to techniques in drawing and coloring. This training activity is carried out with several methods including lectures, demonstrations, and questions and answers, exercises, and assignments. The training on the development of painting creativity was given to students and teachers of SDN 32 Tigo Suku Paninjauan by utilizing the media of used cans, students and teachers can do various forms of drawing and coloring works of art such as pencil holders, piggy banks, garbage cans, tissue holders and others. In addition to being a learning medium, this creativity development training, if pursued, is certainly a business opportunity for teachers and students outside of school